Genomic data from Gentoo penguin ( Pygoscelis papua ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The Gentoo penguin is easily recognized by the wide white stripe extending across the top of its head, and its bright orange-red bill. It has a long tail. Gentoos are the third-largest species of penguin after the Emperor penguin and the King penguin. Gentoos are well adapted to extremely cold and harsh climates. Breeding colonies are located on ice-free surfaces. Gentoos breed on many sub-Antarctic islands, with main colonies are on the Falkland Islands, South Georgia and the South Sandwich Islands, and Kerguelen Islands. Gentoo penguins exhibit population genetic structure, and different populations are occasionally considered to represent several subspecies. They are considered as Least Concern by the International Union for Conservation of Nature (IUCN). We sequenced the genome of an adult Gentoo penguin from West Antarctic Peninsula, Antarctica (provided by Tom Hart) to a depth of approximately 105x with short reads from a series of libraries with various insert sizes (250bp-20Kb). The assembled ...